Revisiting the Manila Galleon, a Chilean Perspective from the XXI Century - Glasinovic Vernon, Juan Pablo (Latin American Journal of Trade Policy, 2019)
The Manila Galleon marked the beginning of globalization as we know it today, linking Asia with the Americas and Europe through trade, from the second half of the XVI century until the first decades of the XIX century. Only a few decades after its discovery and conquest by Spain, the American continent burst onto the global scene allowing quasi industrial production in China and global trade, based on the silver pattern. A combination of circumstances made possible this first wave of globalization, ignited by the Americas. Looking back at that experience, we can better understand the current status of world affairs and extract some important lessons for Latin America in order to recover prominence in the relationship with Asia.